2000
DOI: 10.1128/iai.68.2.463-469.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of a Recombinant Human Immunoglobulin A2 (IgA2)-IgA1 Hybrid Antibody by Certain Bacterial IgA1 Proteases

Abstract: To understand more about the factors influencing the cleavage of immunoglobulin A1 (IgA1) by microbial IgA1 proteases, a recombinant human IgA2/IgA1 hybrid molecule was generated. In the hybrid, termed IgA2/A1 half hinge, a seven-amino-acid sequence corresponding to one half of the duplicated sequence making up the IgA1 hinge was incorporated into the equivalent site in IgA2. Insertion of the IgA1 half hinge into IgA2 did not affect antigen binding capacity or the functional activity of the hybrid molecule, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Previous experiments showed that all the different bacterial IgA1 proteases cleaved recombinant wild-type human IgA1 to give fragments of mass consistent with cleavage in the hinge (22,27). However, recombinant human IgA2 was resistant to cleavage with these enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experiments showed that all the different bacterial IgA1 proteases cleaved recombinant wild-type human IgA1 to give fragments of mass consistent with cleavage in the hinge (22,27). However, recombinant human IgA2 was resistant to cleavage with these enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…A series of mutants were produced based on a hybrid IgA2/IgA1 half hinge Ab in which a sequence representing half of the duplicated hinge region of IgA1 was incorporated into the equivalent position in IgA2 (22) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IgA is a mucosal antibody and can be secreted across barriers in the gut, breast, lungs, GU tract to block pathogens at mucosal surfaces. The major differences between IgA1 and IgA2 lies in the presence of the drastically extended hinge region of IgA1, thought to improve antigen recognition by increasing affinity with antigen epitopes that are spatially distant, but making it vulnerable to proteases 37, 38, 39. The IgE antibody has received an increasing amount of attention because of its role in hypersensivity responses and allergy in the developed world, although initially thought to have evolved to target parasites (eg, helminths and parasitic arthropods) that are too large to be phagocytosed 40, 41, 42…”
Section: Generation Of B Cell Diversitymentioning
confidence: 99%
“…cleavage by proteases derived from bacterial pathogens, such as Haemophilus influenzae and Neisseria meningitidis [20][21][22]. It is currently not known whether SIgA1 and SIgA2 exhibit differential susceptibility to proteolytic cleavage by normal microbial flora in the various mucosal fluids.…”
Section: Structure and Subclasses And Of Igamentioning
confidence: 99%